Implementation of Income Tax (Pph) and Value Added Tax (PPN) in Personnel Operations of the Organizational Bureau of the Regional Secretary of North Sumatra Province - Ahmadi Bi Rahmani, Nur; Wicaksono, M. Fadli (LPPPIPublishing, 2025)
This research analyzes the implementation of Income Tax (PPh) and Value Added Tax (PPN) in the personnel operations of the Organization Bureau of the Regional Secretary of North Sumatra Province. Using a descriptive qualitative literature study method, the research evaluates four key dimensions: regulation, technology, human resources, and internal control systems. The research findings reveal the complexity of tax implementation, including regulatory limitations, digital transformation of e-SPT, human resource competency challenges, and the importance of proactive control systems. The study found that 42% of agencies experience regulation interpretation difficulties, 60% of technological infrastructure is available, but 35% of employees require capacity development. The research generates comprehensive recommendations for tax implementation optimization, including human resource development, technological system improvement, regulatory synchronization, and strengthening internal control mechanisms.